2015
DOI: 10.3389/fcimb.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

The trans-Golgi SNARE syntaxin 10 is required for optimal development of Chlamydia trachomatis

Abstract: Chlamydia trachomatis, an obligate intracellular pathogen, grows inside of a vacuole, termed the inclusion. Within the inclusion, the organisms differentiate from the infectious elementary body (EB) into the reticulate body (RB). The RB communicates with the host cell through the inclusion membrane to obtain the nutrients necessary to divide, thus expanding the chlamydial population. At late time points within the developmental cycle, the RBs respond to unknown molecular signals to redifferentiate into infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Although sphingolipid accumulation in CERT‐KO cells differed between C. psittaci and C. trachomatis , CERT is essential for normal development of both species. Previous studies have shown that an imbalanced transport of nutrients including sphingolipids to the C. trachomatis inclusion had negative effects on the bacterial development (Lucas, Ouellette, Kabeiseman, Cichos, & Rucks, ; Ouellette & Carabeo, ). It remains to be determined how CERT controls sphingolipid acquisition during C. psittaci infections and how an increase in sphingolipids results a less infectious progeny formation in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Although sphingolipid accumulation in CERT‐KO cells differed between C. psittaci and C. trachomatis , CERT is essential for normal development of both species. Previous studies have shown that an imbalanced transport of nutrients including sphingolipids to the C. trachomatis inclusion had negative effects on the bacterial development (Lucas, Ouellette, Kabeiseman, Cichos, & Rucks, ; Ouellette & Carabeo, ). It remains to be determined how CERT controls sphingolipid acquisition during C. psittaci infections and how an increase in sphingolipids results a less infectious progeny formation in this species.…”
Section: Discussionmentioning
confidence: 99%
“…2b). These include the trans -Golgi SNARE proteins syntaxin 6 (STX6) 58,59 and STX10 (REF. 60), vesicle-associated membrane protein 4 (VAMP4), a STX6 binding partner 61 , and GS15 (also known as BET1L) 62 , which regulates the acquisition of nutrients from the Golgi exocytic pathway.…”
Section: Establishing An Intracellular Nichementioning
confidence: 99%
“…Increased expression levels of PLA2 may induce genetic expression of COX-2 for numerous inflammation-stimulating factors, including lipopolysaccharide, IL-1, TNF, epidermal growth factor α and platelet activating factor (21), and increase levels of PGE2, prostacyclin and PGE1 at inflammatory sites. A positive association between COX-2 mRNA and PGE2 levels at inflammatory sites and severity of inflammation has been verified in numerous experiments (22). At present, PGE2 is considered as an important mediator of inflammation.…”
Section: Discussionmentioning
confidence: 71%